New English language arts: communication, technology, and rhetoric in the secondary classroom - Beard, Eric, author; Sounder, Donna, advisor; Frank, Katherine, committee member; Eskew, Doug, committee member (Colorado State University. Libraries, 2010)
In this thesis, I discuss the changing nature of communication in the twenty-first century and how these changes affect English language arts education at the secondary level. I argue that emerging technologies are changing the way people process and produce information, yet the current environment of English language arts in America is stagnant and outdated. A new vision for English language arts must be adopted by teachers, administrators, and policymakers which includes innovative approaches to the goals, pedagogies, curricula, and methods of assessment used in these courses. Educators must look at communication as much more than merely print based writing; the terms “literacy” and “composition” must be expanded to include all of the multifarious ways that people communicate. I also assert that technology and rhetoric must play fundamental roles in these courses because they foster deeper critical thinking and encourage new methods of production. Greater communication between professionals at the secondary and post-secondary levels is essential for this vision to take root, as is solid professional development.
Covers not scanned.
Keywords: English language -- Study and teaching (Secondary)